The role of media, life experience, knowledge and government support in creating Generation Z's pro-environmental behavior in Indonesia - Rahsilaputeri, Maharini -; Sumarwan, Ujang; Hartoyo, Hartoyo; Suharjo, Budi (Center for Science and Technology, Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
As the world’s fourth most populated country, Indonesia will need to use its resources sustainably. Generation Z as the future consumer has a key role to actively engage in pro-environmental behavior to prevent further environmental degradation. This study assessed the role of the media, life experiences, knowledge and government support in the adoption of pro-environmental behavior among generation Z using the Norm Activation Model. Data were collected using an online questionnaire to 590 university students in the greater area of Indonesia capital city, Jakarta. Data were analyzed using descriptive method and PLS-SEM. This study demonstrated the ability of the Norm Activation Model to predict the relationship between the media, life experiences, knowledge and government support to pro-environmental behavior and concluded that knowledge is the key influential factor of personal norms to engage in pro-environmental behavior, followed by the media and significant life experiences, while government has a negative influence. The implications are discussed.